1974
DOI: 10.1088/0022-3727/7/10/314
|View full text |Cite
|
Sign up to set email alerts
|

Growth of ionization currents in nitrogen

Abstract: Townsend's primary and secondary ionization coefficients α/p and γ were determined in nitrogen over a wide range of E/p (100-1000 V cm−1 Torr−1) and p (0·4 to 12 Torr at 0 °C) using the pressure variation technique. This technique, along with the Gosseries method of evaluation of ionization coefficients, seems to be more suitable at higher values of E/p, since the errors in these coefficients could be minimized by a suitable selection of p and d, thus eliminating the non-equilibrium ionization condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
5
10
0
1
Order By: Relevance
“…The ionization coefficient α/N as a function of E/N values calculated in the present work, are shown in figure (14) in comparison with experimental values (Raju, 2012), (Maller and Naidu, 1974), (Rao and Raju, 1973), (Qiu et al, 1989). It can be seen that they are agree quit well with the present results.…”
Section: Dichlorodifluoromethan CCL 2 Fsupporting
confidence: 88%
See 2 more Smart Citations
“…The ionization coefficient α/N as a function of E/N values calculated in the present work, are shown in figure (14) in comparison with experimental values (Raju, 2012), (Maller and Naidu, 1974), (Rao and Raju, 1973), (Qiu et al, 1989). It can be seen that they are agree quit well with the present results.…”
Section: Dichlorodifluoromethan CCL 2 Fsupporting
confidence: 88%
“…The variation of electron characteristic energy values in CCl 2 F 2 as a function of E/N values are shown in figure (13). As shown in figure there's difference between present calculation and experimental results of (Naidu and Prasad, 1969), (Maller and Naidu, 1974), but there is good agreement with experimental results of (Raju, 2012).…”
Section: Dichlorodifluoromethan CCL 2 Fsupporting
confidence: 52%
See 1 more Smart Citation
“…The latter results agree with the ones by Ryzko [31] who also measured an increase (with respect to dry air) in the electron drift velocity in moist air kept at 293 K, a pressure of 16 Torr and for E/N between 120 and 150 Td. The measurements done by Maller et al [38] in dry and humid air (with a relative humidity of 55%) at 293 K, pressures varying between 0.4 and 3.2 Torr and for E/N between 60 and 1500 Td show that the characteristic energy (D T /µ) in humid air exhibits a slight enhancement (of maximum 15% at 60 Td) above the dry case for values of E/N below 250 Td. The work by Raja Rao et al [39] reported experimental results for the ionization coefficient α/N in dry and humid air (at atmospheric pressure with a relative humidity of 56% and 293 K (room temperature)) for E/N between 153 and 2750 Td showing that α/N is higher in humid air.…”
Section: Electron Transport Coefficientsmentioning
confidence: 97%
“…Além da técnica de variação da distância, os estudos do crescimento da corrente em SST podem ser realizados em termos da variação do número de moléculas do gás N (ou da variação da pressão) [27]. Para isso, a Eq.…”
Section: Corrente Em Função Da Densidade Do Gásunclassified